Manufacturing method for all-solid-state batteries

JP7639663B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021186716
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-17
Publication Date
2025-03-05
Estimated Expiration
2041-11-17

AI Technical Summary

Benefits of technology

【0008】 本開示は、全固体電池のエネルギー密度を向上させることができる全固体電池の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639663000002
    Figure 0007639663000002
  • Figure 0007639663000003
    Figure 0007639663000003
  • Figure 0007639663000004
    Figure 0007639663000004
Patent Text Reader

Abstract

To provide a manufacturing method of an all-solid battery, capable of improving energy density of the all-solid battery.SOLUTION: A manufacturing method of an all-solid battery, having a first electrode layer, a solid-state electrolyte layer, a second electrode layer, and a second collector on both surfaces of a first collector in this order, contains: a step of obtaining a lamination body into which the first electrode layer, the solid-state electrolyte layer, the second electrode layer are laminated in this order onto both surfaces of the first collector; a step of forming a one surface by cutting at least one side surface of a lamination direction of the lamination body; a step of arranging an insulation layer to a region adjacent to a scheduled region where the lamination body is arranged onto the surface of the second collector, and forming a bonding body of the second collector and the insulation layer; and a step of arranging the lamination body so that the second electrode layer is contacted to the second collector to the scheduled region where the lamination body is arranged onto the surface of the second collector, and bonding the insulation layer with the side surface as one surface of the lamination body.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing an all-solid-state battery. [Background technology]

[0002] All-solid-state batteries have attracted attention because they use a solid electrolyte instead of an electrolytic solution containing an organic solvent as the electrolyte between the positive and negative electrodes.

[0003] Patent Document 1 discloses an all-solid-state battery having an adhesive means for adhering a current collector to a battery unit stacked adjacent to the current collector. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-204377 A Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand for improving the energy density of all-solid-state batteries. In an electrode laminate in which a negative electrode, a solid electrolyte layer, and a positive electrode are laminated, if the electrode laminate is cut into a single piece and the sides are made flush, and then the sides are fixed with an insulating layer such as tape, the insulating layer may protrude onto the surface of the positive electrode, and the excess insulating layer on the surface of the positive electrode may apply a local load to the electrode laminate. Also, the extra insulating layer on the surface of the positive electrode increases the size of the solid-state battery, reducing the energy density of the solid-state battery.

[0006] The present disclosure has been made in consideration of the above-described circumstances, and has a main object to provide a manufacturing method for an all-solid-state battery that can improve the energy density of the all-solid-state battery. [Means for solving the problem]

[0007] The method for producing an all-solid-state battery disclosed herein is a method for producing an all-solid-state battery having a first electrode layer, a solid electrolyte layer, a second electrode layer, and a second current collector, in this order, on both sides of a first current collector, the method comprising: a step of obtaining a laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are laminated in this order on both sides of the first current collector; A step of making at least one side surface of the laminate in the stacking direction of the laminate flush by cutting; disposing an insulating layer on a surface of the second current collector in an area adjacent to an area where the laminate is to be disposed, to form a bonded body of the second current collector and the insulating layer; The method is characterized by comprising a step of: placing the laminate in a region on the surface of the second current collector where the laminate is to be placed so that the second electrode layer is in contact with the second current collector; and adhering the insulating layer to a side surface of the laminate that is flush with the surface of the laminate. Effect of the Invention

[0008] The present disclosure can provide a method for producing an all-solid-state battery that can improve the energy density of the all-solid-state battery. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a flowchart showing an example of a method for producing an all-solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a diagram showing an example of a laminate before a cutting process. [Diagram 3] FIG. 3 is a diagram showing an example of the laminate after the cutting step. [Figure 4] FIG. 4 is a diagram showing an outline of the (3) bonded body forming step and (4) bonding step in Example 1. [Diagram 5] FIG. 5 is a diagram showing an outline of (3) the bonded body forming step and (4) the bonding step in Example 2. [Figure 6] FIG. 6 is a diagram showing an outline of (3) the bonded body forming step and (4) the bonding step in Example 3. [Figure 7] FIG. 7 is a diagram showing an outline of (3) the bonded body forming step and (4) the bonding step in Comparative Example 1. As shown in FIG. [Figure 8] FIG. 8 is a diagram showing an outline of (3) bonded body forming step and (4) bonding step in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The method for producing an all-solid-state battery disclosed herein is a method for producing an all-solid-state battery having a first electrode layer, a solid electrolyte layer, a second electrode layer, and a second current collector, in this order, on both sides of a first current collector, the method comprising: a step of obtaining a laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are laminated in this order on both sides of the first current collector; A step of making at least one side surface of the laminate in the stacking direction of the laminate flush by cutting; disposing an insulating layer on a surface of the second current collector in an area adjacent to an area where the laminate is to be disposed, to form a bonded body of the second current collector and the insulating layer; The method is characterized by comprising a step of: placing the laminate in a region on the surface of the second current collector where the laminate is to be placed so that the second electrode layer is in contact with the second current collector; and adhering the insulating layer to a side surface of the laminate that is flush with the surface of the laminate.

[0011] 1 is a flowchart showing an example of a method for producing an all-solid-state battery according to the present disclosure, in which 11 denotes a first current collector, 12 denotes a first electrode layer, 13 denotes a solid electrolyte layer, 14 denotes a second electrode layer, 15 denotes a second current collector, and 16 denotes an insulating layer. As shown in FIG. 1, the method for producing an all-solid-state battery according to the present disclosure includes (1) a laminate obtaining step, (2) a cutting step, (3) a bond forming step, and (4) a bonding step. The (3) bonded body forming step may be performed before the (4) bonding step, and may be performed before, simultaneously with, or after the (1) laminate obtaining step, and may be performed before, simultaneously with, or after the (2) cutting step.

[0012] (1) Laminated body obtaining process The laminate obtaining step is a step of obtaining a laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are laminated in this order on both sides of the first current collector. The first electrode layer can be a positive electrode layer or a negative electrode layer. When the first electrode layer is a positive electrode layer, the second electrode layer, which is its counter electrode layer, is a negative electrode layer, and when the first electrode layer is a negative electrode layer, the second electrode layer is a positive electrode layer. The method for laminating the first electrode layer, the solid electrolyte layer, and the second electrode layer in this order on both sides of the first current collector is not particularly limited, and any conventionally known method can be appropriately adopted.

[0013] (2) Cutting process The cutting step is a step of cutting at least one side surface in the stacking direction of the laminate to make it flush. The cutting method is not particularly limited, and examples thereof include laser irradiation. The side surfaces to be flush with each other need only be at least one side surface, and may be only one side surface.

[0014] (3) Joined body formation process The bonded body forming step is a step of arranging an insulating layer in an area adjacent to an area on the surface of the second current collector where the laminate is to be arranged, and forming a bonded body of the second current collector and the insulating layer. The joining method is not particularly limited, and when the insulating layer has adhesive properties, the second current collector and the insulating layer may be bonded to each other. In the all-solid-state battery, the second current collector has a region that does not face the laminate and a region that faces the laminate, i.e., the dimension of the second current collector in the planar direction is larger than the dimension of the laminate in the planar direction. The position at which the insulating layer is placed is not particularly limited as long as it is an area adjacent to the area on the surface of the second current collector where the laminate is intended to be placed, and it may be a position where it can be adhered to the flush side of the laminate in the bonding process described below. The thickness of the insulating layer (height in the stacking direction) may be the same as or different from the thickness of the laminate (height in the stacking direction), and may be within the range of the thickness of the laminate ± the thickness of the second electrode layer. When the thickness of the insulating layer is greater than the thickness of the laminate, the thickness of the insulating layer may be adjusted to be approximately the same as the thickness of the laminate by pressing, heating, etc. This allows the height of the laminate and the insulating layer to be matched.

[0015] The material of the insulating layer may be any material having insulating properties, may be any material having adhesive properties, or may be an adhesive. The adhesive used for the insulating layer is not particularly limited as long as it is solid and has an adhesive function. Examples of the adhesive include a resin having tackiness and a hot melt agent. Examples of the resin having tackiness include an acrylic resin, a rubber resin, a silicone resin, and a urethane resin. The hot melt agent is not particularly limited as long as it is a resin having a melting point of 140° C. or less, and examples of the hot melt agent include an ethylene-vinyl acetate resin, a polyethylene naphthalate resin, and the like.

[0016] (4) Adhesion process The bonding process is a process of placing the laminate in the area on the surface of the second current collector where the laminate is to be placed so that the second electrode layer is in contact with the second current collector, and bonding the insulating layer to a side surface of the laminate that is flush with the surface of the laminate. The insulating layer can be used as a positioning member when placing the laminate on the surface of the second current collector. The bonding method is not particularly limited, and the insulating layer and the laminate may be bonded via an adhesive, or if the insulating layer itself has adhesive properties, the laminate and the insulating layer may be bonded directly to each other.

[0017] [Electrode layer] The electrode layer contains an electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The electrode layer is a positive electrode layer or a negative electrode layer. Two electrode layers having different types of electrode active materials may be prepared, and one may be used as a positive electrode layer and the other as a negative electrode layer. As the electrode active material, any material that can be used as an active material for an all-solid-state battery can be used, and materials similar to those exemplified as the positive electrode active material and the negative electrode active material described later can be used. As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer described later can be exemplified. Examples of the conductive material and binder include the same materials as those exemplified for the positive electrode layer described below. The thickness of the electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm.

[0018] [Current collector] As the current collector, the same ones as those exemplified as the positive electrode current collector and the negative electrode current collector described later can be used.

[0019] [All-solid battery] The all-solid-state battery of the present disclosure may include a positive electrode including a positive electrode layer and a positive electrode current collector, a solid electrolyte layer, and a negative electrode including a negative electrode layer and a negative electrode current collector. The all-solid-state battery has a first electrode layer, a solid electrolyte layer, a second electrode layer, and a second current collector, in this order, on both sides of a first current collector. One of the first and second electrode layers is a positive electrode layer and the other is a negative electrode layer. The first current collector is a positive electrode current collector if the first electrode layer is a positive electrode layer, and is a negative electrode current collector if the first electrode layer is a negative electrode layer. The second current collector is a positive electrode current collector if the second electrode layer is a positive electrode layer, and is a negative electrode current collector if the second electrode layer is a negative electrode layer. The all-solid-state battery may be a battery unit in which a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, a negative electrode current collector, a negative electrode layer, a solid electrolyte layer, a positive electrode layer, and a positive electrode current collector are stacked in this order. The all-solid-state battery may be a battery unit in which a negative electrode current collector, a negative electrode layer, a solid electrolyte layer, a positive electrode layer, a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector are stacked in this order. The all-solid-state battery may be a stack of two or more battery units.

[0020] [Positive electrode] The positive electrode includes a positive electrode layer and a positive electrode current collector.

[0021] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain optional components such as a solid electrolyte, a conductive material, and a binder.

[0022] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include metallic lithium (Li), lithium alloys, LiCoO2, and LiNi. 0.8 Co 0.15 Al 0.05 O2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 The lithium metal phosphates are, for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. The transition metal oxides are, for example, V2O5, and MoO3. The lithium storage intermetallic compounds are, for example, Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more, or 90% or more of the surface of the positive electrode active material.

[0023] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0024] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.

[0025] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0026] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm.

[0027] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a slurry for the positive electrode layer, and the slurry for the positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of the support is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0028] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0029] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for an all-solid-state battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0030] [Negative electrode] The negative electrode includes a negative electrode layer and a negative electrode current collector.

[0031] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, soft carbon, lithium, lithium alloys, Si, Si alloys, and Li4Ti5O 12As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.

[0032] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, such as SUS, copper, and nickel. The shape of the negative electrode current collector may be, for example, a foil or a plate. The planar shape of the negative electrode current collector is not particularly limited, and may be, for example, a circle, an ellipse, a rectangle, or any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0033] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.

[0034] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.

[0035] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.

[0036] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The heat treatment method is not particularly limited, and for example, a method using a firing furnace can be mentioned.

[0037] Examples of the oxide-based solid electrolyte include solid electrolytes containing Li element, Y element (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, S), and O element. Specific examples of the oxide-based solid electrolyte include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 and other garnet-type solid electrolytes; perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, (Li,Sr)(Ta,Zr)O3; NASICON-type solid electrolytes such as Li(Al,Ti)(PO4)3, Li(Al,Ga)(PO4)3; Li-P-O-based solid electrolytes such as Li3PO4, LIPON (a compound in which a part of O in Li3PO4 is replaced by N); Li-B-O-based solid electrolytes such as Li3BO3 and a compound in which a part of O in Li3BO3 is replaced by C.

[0038] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. Examples of the complex anion include (BH4) - , (NH2) - , (AlH4) - , and (AlH6) 3- and the like. Examples of the halide-based solid electrolyte include Li 6-3z Y z X6 (X is at least one of Cl and Br, and z satisfies 0 < z < 2) and the like. Examples of the nitride-based solid electrolyte include Li3N and the like.

[0039] From the viewpoint of good handleability, the shape of the solid electrolyte may be particulate. The average particle size of the solid electrolyte particles is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more, while the average particle size of the solid electrolyte particles is, for example, 25 μm or less, and may be 10 μm or less.

[0040] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0041] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.

[0042] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.

[0043] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method of forming the solid electrolyte layer includes a method of applying a slurry for the solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support can be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.

[0044] The all-solid-state battery may include an exterior body that houses the laminate, a restraining member, and the like, as necessary. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a restraining member for an all-solid-state battery, as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.

[0045] The all-solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The all-solid-state battery may be an all-solid-state lithium secondary battery or an all-solid-state lithium ion secondary battery. Examples of the shape of the all-solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the all-solid-state battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The all-solid-state battery of the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices. EXAMPLES

[0046] Example 1 [Preparation of positive electrode layer] Using a rolling fluidized coating device (Powrex Corporation), the positive electrode active material particles (Li 1.15 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 The researchers coated the particles (which have O2 as the main phase) with lithium niobate and sintered them in an air atmosphere to obtain positive electrode active material particles with a lithium niobate coating layer. PVdF, the above positive electrode active material particles, a sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic), and VGCF (manufactured by Showa Denko K.K.) were added to a polypropylene container, and the resulting slurry for the positive electrode layer was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Corporation). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the slurry for the positive electrode layer was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the slurry for the positive electrode layer was applied to the aluminum foil by the blade method using an applicator. Then, the slurry for the positive electrode layer was naturally dried and dried for 30 minutes on a hot plate at 100 ° C. to obtain a positive electrode mixture on the aluminum foil (substrate). The laminate of the aluminum foil (substrate) and the positive electrode mixture was densified at 4t / cm to obtain a positive electrode layer on the aluminum foil (substrate). The amount of the slurry for the positive electrode layer applied was adjusted so that the thickness of the positive electrode layer obtained when the positive electrode mixture was densified at 4t / cm was 15 μm.

[0047] [Preparation of negative electrode] In a polypropylene container, PVdF, negative electrode active material particles (Li4Ti5O 12 (LTO) particles) and the same sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic) as above were added, and the obtained slurry for the negative electrode layer was stirred for 30 minutes with an ultrasonic dispersion device. The slurry for the negative electrode layer was applied to copper foil by the blade method using an applicator. The slurry for the negative electrode layer was then naturally dried and dried on a hot plate at 100°C for 30 minutes to obtain a negative electrode having a negative electrode layer on the copper foil (negative electrode current collector). The slurry for the negative electrode layer was then similarly applied to the back side of the copper foil (negative electrode current collector) and dried to form a negative electrode layer on the back side of the copper foil (negative electrode current collector).

[0048] [Preparation of solid electrolyte layer] Heptane, BR, and a sulfide-based solid electrolyte (Li2S-P2S5-based glass ceramic) were added to a polypropylene container, and the resulting solid electrolyte layer slurry was stirred for 30 seconds with an ultrasonic dispersion device. Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the solid electrolyte layer slurry was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the solid electrolyte layer slurry was applied onto an aluminum foil by a blade method using an applicator. Then, the solid electrolyte layer slurry was naturally dried and dried on a hot plate at 100°C for 30 minutes to form a solid electrolyte layer on the aluminum foil as a substrate.

[0049] [Laminated body production] (1) Laminated body obtaining process The solid electrolyte layers were laminated on both sides of the negative electrode so that each negative electrode layer and each solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each solid electrolyte layer. Next, the positive electrode layer was laminated on each solid electrolyte layer so that each positive electrode layer and each solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each positive electrode layer to obtain a laminate.

[0050] (2) Cutting process The obtained laminate was pressed at 5 t / cm and 170°C. Thereafter, the laminate was laser trimmed so that the positive electrode layer had a size of 70.0 mm × 71.0 mm, and the laminate was cut so that the negative electrode had a size of 72.0 mm × 72.0 mm. Then, a negative electrode terminal was welded to one side surface of the laminate. FIG. 2 is a diagram showing an example of a laminate before a cutting process. FIG. 3 is a diagram showing an example of the laminate after the cutting step. As shown in FIG. 3, the laminate was cut along the cutting lines shown in FIG. 2 so that the side opposite to the side to which the negative electrode terminal was welded would be flush with the positive electrode layer size of 70.0 mm × 70.0 mm, thereby obtaining a laminate with a total thickness of 130 μm.

[0051] (3) Joined body formation process 4 is a diagram showing an outline of the (3) joint formation step and (4) adhesion step in Example 1. Reference numeral 20 denotes a positive electrode current collector foil, 21 denotes double-sided tape No. 5605, 22 denotes Q51, 30 denotes a positive electrode layer, 40 denotes a laminate of solid electrolyte layer-negative electrode layer-negative electrode current collector+negative electrode terminal-negative electrode layer-solid electrolyte layer, 41 denotes a negative electrode terminal, and 50 denotes a laminate of positive electrode layer-solid electrolyte layer-negative electrode layer-negative electrode current collector+negative electrode terminal-negative electrode layer-solid electrolyte layer-positive electrode layer. An insulating layer was prepared by laminating two layers (thickness 100 μm) of polyethylene naphthalate film Q51 (thickness 50 μm) manufactured by Teijin DiPont and double-sided tape No. 5605 (thickness 50 μm) manufactured by Nitto Denko Corporation, where the depth of Q51 was greater than the depth of the positive electrode current collector foil and the depth of double-sided tape No. 5605 was smaller than the depth of the positive electrode current collector foil. The thickness of the insulating layer (100 μm) was smaller than the thickness of the laminate (130 μm). The insulating layer was cut to a width of 3 mm, and the insulating layer was attached to an area (position 70 to 72 mm in the surface direction from the negative terminal side) adjacent to the area on the surface of the positive current collector foil where the laminate was to be placed, so that the double-sided tape No. 5605 was in contact with the positive current collector foil as a second current collector, thereby forming a joint between the positive current collector foil and the insulating layer.

[0052] (4) Adhesion process A hot melt material was applied onto the positive current collector foil. Then, using the insulating layer (tape) as a reference for positioning the laminate on the surface of the positive current collector foil, the laminate was placed in the area on the surface of the positive current collector foil where the laminate was to be placed so that the second electrode layer was in contact with the positive current collector foil, and the flush side of the laminate was brought into contact with the insulating layer, and the insulating layer and the flush side of the laminate were bonded together. These were then heated at 140°C, and the positive current collector foil and the laminate were bonded and fixed with the hot melt material. Thereafter, another positive electrode current collector foil was placed on the opposite side of the stacking direction to the positive electrode current collector foil side of the laminate via a hot melt material, and these were pressed together under conditions of 140°C and 5 MPa, the positive electrode terminal was welded, and then these were vacuum sealed to obtain an all-solid-state battery. Thereafter, the resistance of the all-solid-state battery was measured to check whether or not a short circuit had occurred.

[0053] Example 2 5 is a diagram showing an outline of the (3) bonded body forming step and (4) bonding step of Example 2. The numbers in FIG. 5 have the same meanings as those in FIG. In the above (3) joint formation step, an insulating layer was prepared which was a three-layer laminate (thickness 150 μm) of Nitto Denko double-sided tape No. 5605 (thickness 50 μm), Teijin DiPont polyethylene naphthalate film Q51 (thickness 50 μm), and Nitto Denko double-sided tape No. 5605 (thickness 50 μm), in which the depth of Q51 was greater than the depth of the positive electrode current collector foil, and the depth of double-sided tape No. 5605 was smaller than the depth of the positive electrode current collector foil. The thickness of the insulating layer (150 μm) was greater than the thickness of the laminate (130 μm). An all-solid-state battery was obtained in the same manner as in Example 1, except that the insulating layer was cut to a width of 3 mm, and the insulating layer was attached to an area adjacent to an area on the surface of the positive electrode current collector foil where the laminate was to be placed so that one side of the double-sided tape No. 5605 was in contact with the positive electrode current collector foil serving as a second current collector, thereby forming an assembly of the positive electrode current collector foil and the insulating layer.

[0054] Example 3 6 is a diagram showing an outline of (3) the bonded body forming step and (4) the bonding step in Example 3. 23 indicates Hibon ZH234-1, and the other numerals in FIG. 6 have the same meanings as in FIG. In the above (3) bonded body forming step, the insulating layer was prepared by pressing Hitachi Chemical's Hibon ZH234-1 together with a spacer having a thickness of 140 μm at a temperature of 120° C. The thickness of the insulating layer (140 μm) was greater than the thickness of the laminate (130 μm). The insulating layer was cut to a width of 3 mm, and the insulating layer was attached to an area adjacent to the area on the surface of the positive electrode current collector foil where the laminate was to be placed, using a butyl butyrate solution containing PVDF as a binder, to form a bonded body of the positive electrode current collector foil and the insulating layer. Except for this, an all-solid-state battery was obtained in the same manner as in Example 1.

[0055] Comparative Example 1 7 is a diagram showing an outline of the (3) bonded body forming step and (4) bonding step of Comparative Example 1. The numbers in FIG. 7 have the same meanings as those in FIG. In the above (4) bonding step, a position 1 mm from the end of the positive electrode layer on the negative electrode terminal side of the laminate toward the center in the surface direction was set as a reference position for laminating with the positive electrode current collector, and the laminate was placed on the positive electrode current collector foil so that the region from the end of the positive electrode layer on the negative electrode terminal side of the laminate toward the center in the surface direction of 1 mm did not face the positive electrode current collector foil, and the positive electrode current collector foil and the laminate were fixed. That is, in the above (3) joining step, a part of the insulating layer (1 mm wide) was placed in the region on the surface of the positive electrode current collector foil where the laminate was to be placed (69 to 71 mm from the negative electrode terminal side, not 70 to 72 mm in the surface direction). Except for this, an all-solid-state battery was obtained in the same manner as in Example 1.

[0056] Comparative Example 2 8 is a diagram showing an outline of (3) bonded body forming step and (4) bonding step of Comparative Example 2. The numbers in FIG. 8 have the same meanings as those in FIG. In the above (4) bonding step, a position 2 mm from the end of the positive electrode layer on the negative electrode terminal side of the laminate toward the center in the surface direction was set as a reference position for laminating with the positive electrode current collector, and the laminate was placed on the positive electrode current collector foil so that the region from the end of the positive electrode layer on the negative electrode terminal side of the laminate toward the center in the surface direction of 2 mm did not face the positive electrode current collector foil, and the positive electrode current collector foil and the laminate were fixed. That is, in the above (3) joining step, a part of the insulating layer (2 mm wide) was placed in the region on the surface of the positive electrode current collector foil where the laminate was to be placed (68 to 70 mm from the negative electrode terminal side, not 70 to 72 mm in the surface direction). Except for this, an all-solid-state battery was obtained in the same manner as in Example 1.

[0057] [Evaluation method] Ten samples of each of the all-solid-state batteries of Examples 1 to 3 and Comparative Examples 1 to 2 were prepared, and the resistance of each was measured to confirm the number of samples in which a short circuit occurred and the number of samples in which an overlap between the positive electrode layer and the insulating layer occurred. These results are shown in Table 1.

[0058] [Table 1]

[0059] [Evaluation Results] As shown in Table 1, it can be seen that no short circuit occurred and no overlapping of the positive electrode layer and the insulating layer occurred in the all-solid-state batteries of Examples 1 to 3. Therefore, according to the manufacturing method of the present disclosure, it is possible to improve the energy density of the all-solid-state battery. [Explanation of symbols]

[0060] 11 First current collector 12 1st electrode layer 13 Solid electrolyte layer 14 Second electrode layer 15 Second current collector 16 Insulating layer 20 Positive electrode current collector foil 21 Double-sided tape No. 5605 22 Q51 23 Hibon ZH234-1 30 Positive electrode layer 40 Laminate of solid electrolyte layer-negative electrode layer-negative electrode current collector+negative electrode terminal-negative electrode layer-solid electrolyte layer 41 Negative terminal 50 Laminate of positive electrode layer-solid electrolyte layer-negative electrode layer-negative electrode current collector+negative electrode terminal-negative electrode layer-solid electrolyte layer-positive electrode layer

Claims

[Claim 1] A method for producing an all-solid-state battery having a first electrode layer, a solid electrolyte layer, a second electrode layer, and a second current collector, in this order, on both sides of a first current collector, the method comprising the steps of: obtaining a laminate in which the first electrode layer, the solid electrolyte layer, and the second electrode layer are laminated in this order on both sides of the first current collector; A step of making at least one side surface of the laminate in the lamination direction of the laminate flush by cutting; disposing an insulating layer on a surface of the second current collector in an area adjacent to an area where the laminate is to be disposed, to form a bonded body of the second current collector and the insulating layer; disposing the laminate in a region on a surface of the second current collector where the laminate is to be disposed such that an entire region of a surface of the second electrode layer facing the second current collector is in contact with the second current collector, and bonding the insulating layer to a side surface of the laminate that is flush with the surface of the laminate.

Citation Information

Patent Citations

  • Current collector and laminated battery

    JP2011100693A

  • All-solid battery manufacturing method

    JP2017130281A

  • All-solid battery

    JP2017204377A

  • Laminated battery

    JP2021057321A

  • All solid-state battery and method of manufacturing same

    WO2013035519A1